2013
DOI: 10.29242/spec.339
|View full text |Cite
|
Sign up to set email alerts
|

SPEC Kit 339: Innovation and R&D (December 2013)

Abstract: Supporting Effective Library Management for Over 40 YearsCommitted to assisting research and academic libraries in the continuous improvement of management systems, ARL has worked since 1970 to gather and disseminate the best practices for library needs. As part of its commitment, ARL maintains an active publications program best known for its SPEC Kits. Through the Collaborative Research/Writing Program, librarians work with ARL staff to design SPEC surveys and write publications. Originally established as an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…These tools (e.g., [9]) are extremely useful when fUML is used to specify behavior of user models. However, when fUML is used as a VM, techniques similar to those used for asm.js [10] may be used to increase performance: definition of a simpler subset of fUML, and ahead-of-time compilation to machine code. Therefore, performance should not be an issue that prevents using fUML as proposed in this paper.…”
Section: Resultsmentioning
confidence: 99%
“…These tools (e.g., [9]) are extremely useful when fUML is used to specify behavior of user models. However, when fUML is used as a VM, techniques similar to those used for asm.js [10] may be used to increase performance: definition of a simpler subset of fUML, and ahead-of-time compilation to machine code. Therefore, performance should not be an issue that prevents using fUML as proposed in this paper.…”
Section: Resultsmentioning
confidence: 99%
“…Those could be a mobile profile, which tries to avoid additional decoding, or a desktop profile, exploiting browser's built-in compression capabilities. Considering the potential speedup of future devices and JavaScript (e.g., through asm.js [Herman et al 2013]), another profile could also provide more sophisticated encoders to achieve far better compression rates.…”
Section: Discussionmentioning
confidence: 99%
“…For their sample, 69 percent of the libraries were investing in R&D activities; however, many of these libraries indicated that R&D is diffused throughout the organization. 71 This diffuse approach makes it very difficult to manage and track R&D activities and is likely to produce incremental innovations that reflect the immediate needs of the specific unit. Research into R&D processes has found that the more autonomous exploratory teams are more effective.…”
mentioning
confidence: 99%